Teachers’ work-family conflict efficacy in Malaysia: Scale validation - Ismail, Zanariah; Nordin, Mohamad Sahari (Centre for Promoting Ideas, USA, 2012)
The current research study aims to construct-validate the measurement scale of work-family conflict Self-efficacy of Malaysian married female teachers’. The study attempted to see if the same one-factor structure, which characterized teacher work-family conflict efficacy (WFCE), existed among Malaysian teachers. The sample was selected among 245 married female teachers from secondary schools in Hulu Langat district. Data was collected using self-report questionnaires measuring WFCE. The data was analyzed using the Confirmatory factor Analysis (CFA) procedures and the results confirmed that the one-factor measurement model of WFC efficacy and the six observed variables or items were found to represents teachers’ WFC efficacy construct. Further discussion on the theoretical, methodological and implications were also explained. Keywords: work-family conflict efficacy, confirmatory factor analysis